Enhanced Myocardial Tissue Visualization: A Comparative Cardiovascular Magnetic Resonance Study of Gradient-Spin Echo-STIR and Conventional STIR Imaging - Sadegh Dehghani; Shapoor Shirani; Elahe Jazayeri Gharebagh (International Journal of Biomedical Imaging)
Purpose. This study is aimed at evaluating the efficacy of the gradient-spin echo- (GraSE-) based short tau inversion recovery (STIR) sequence (GraSE-STIR) in cardiovascular magnetic resonance (CMR) imaging compared to the conventional turbo spin echo- (TSE-) based STIR sequence, specifically focusing on image quality, specific absorption rate (SAR), and image acquisition time. Methods. In a prospective study, we examined forty-four normal volunteers and seventeen patients referred for CMR imaging using conventional STIR and GraSE-STIR techniques. Signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), image quality, T2 signal intensity (SI) ratio, SAR, and image acquisition time were compared between both sequences. Results. GraSE-STIR showed significant improvements in image quality (4.15±0.8 vs. 3.34±0.9, p=0.024) and cardiac motion artifact reduction (7 vs. 18 out of 53, p=0.038) compared to conventional STIR. Furthermore, the acquisition time (27.17±3.53 vs. 36.9±4.08 seconds, p=0.041) and the local torso SAR (<13% vs. <17%, p=0.047) were significantly lower for GraSE-STIR compared to conventional STIR in short-axis plan. However, no significant differences were shown in T2 SI ratio (p=0.141), SNR (p=0.093), CNR (p=0.068), and SAR (p=0.071) between these two sequences. Conclusions. GraSE-STIR offers notable advantages over conventional STIR sequence, with improved image quality, reduced motion artifacts, and shorter acquisition times. These findings highlight the potential of GraSE-STIR as a valuable technique for routine clinical CMR imaging.